SISTEM KOMUNIKASI INTERPERSONAL DALAM ORGANISASI LEMBAGA DAKWAH KAMPUS DI UIN SYARIF HIDAYATULLAH JAKARTA - Anisa Aulia; Nasichah Nasichah; Avifah Sauqiyah; Andri Febrian Nugraha (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The purpose of this study is to address the roles and functions of interpersonal communication in an organization, one of which is the LDK organization at UIN Syarif Hidayatullah Jakarta. This research was conducted using a qualitative research method where this method was carried out by interviewing several people as resource persons. The results of this study also explain that interpersonal communication is very important in an organization because it will build harmony in an organization and improve the way a person respects other people both in terms of opinions, thoughts and behavior. The more often a person communicates interpersonally, the more often a person will understand each other's nature and avoid delays in getting information. With interpersonal communication a relationship will last a long time because of the exchange of information and each other's opinions on a problem.